The performance of students from the public network of Bahia in ENEM´s writing: a descriptive approach from the Bahian Education Evaluation System (Olhar de Professor, 2022)
This study aims to present data from a descriptive study that compares the text production performance of students from the state public school system in a state external evaluation with their performance in the Enem essay, in a municipality in Bahia, The research also describes the performance of students from the same educational network, in different years of Enem, with the objective to verify whether there have been advances in the writing of dissertation-argumentative texts. The methodological approach was quantitative and based on a case study (ANDRÉ, 1995), whose descriptive analysis was produced from students’ performance report cards, data from SEC/BA and Inep/MEC. The results revealed a classification of texts considered intermediate, both in the state assessment and in Enem, as well as the leveling of the performance of students from Bahia in the period 2013-2019. Finally, scholars in the field of text (ANTUNES 2005; MARCHUSCHI 2008; KOCH, 2007; FIORIN&PLATÃO, 2011 etc.) signal that the difficulty in producing texts is, in general, a problem for Brazilian students.
Keywords: ENEM Writing. Performance. External Evaluation. Public network.